Developing empathy and support for students with the “most challenging behaviors:” Mixed-methods outcomes of professional development in trauma-informed teaching practices - Koslouski, Jessica B. (Frontiers in Education, 2022)
This mixed-methods study investigated the learning and shifts in teaching practices that educators reported after participating in a trauma-informed schools professional development intervention. Training participants were 61 educators at a suburban U.S. elementary school. The year-long intervention included three after-school trainings, classroom coaching for a subset of teachers, and evaluation of school policies with administrators. Interview (n = 16) and survey (n = 22) data were collected. Quantitative results indicated that educators reported substantial shifts in their thinking and teaching practices. Almost half reported that their thinking shifted a lot and 55% reported that their practices shifted somewhat. Qualitative themes demonstrated increased understandings of trauma and secondary traumatic stress; increased empathy for students, families, colleagues, and compassion for self; enacting proactive strategies; reappraising interactions with students; increased collaboration with colleagues; and enacting self-care strategies as a result of participating in the professional development intervention. Results have implications for policy and practice, particularly the need for implementation and evaluation of trauma-informed approaches during and after the COVID-19 pandemic.